Post-stagnation-point boundary layer flow and mixed convection heat transfer over a vertical, linearly stretching sheet - Ishak, A.; Nazar, R.; Pop, I. (Archives of Mechanics, 2008)
A theoretical analysis is made for the steady two-dimensional post-stagnationpoint flow of an incompressible viscous fluid over a stretching vertical sheet in its own plane. The stretching velocity, the free stream velocity and the surface temperature are assumed to vary linearly with the distance from the stagnation point. The governing partial differential equations are transformed into a coupled system of ordinary differential equations, which is then solved numerically by a finite-difference method. Results are presented in terms of the skin friction coefficient and local Nusselt number, along with a selection of velocity and temperature profiles. It was shown that for both cases of a fixed surface (ε = 0) and a stretching surface (ε ≠ 0), dual solutions exist for the assisting flow (positive values of the buoyancy parameter λ), besides that usually reported in the literature for the opposing flow (λ < 0). It was also found that for the assisting flow, a solution exists for all values of λ (> 0), while for the opposing flow, a solution exists only if the magnitude of the buoyancy parameter is small.